Understanding the course of persistent symptoms in schizophrenia: Longitudinal findings from the pattern study. (September 2018) - Haro, Josep Maria; Altamura, Carlo; Corral, Ricardo; Elkis, Helio; Evans, Jonathan; Krebs, Marie-Odile; Zink, Mathias; Malla, Ashok; Méndez, José Ignacio; Bernasconi, Corrado; Lalonde, Justine; Nordstroem, Anna-Lena
Highlights: Persistent negative symptoms and symptomatic remission were most common states. Despite treatment, schizophrenia symptoms remain stable without overall improvement. Attainment of full symptomatic remission in schizophrenia is challenging. Abstract: The Pattern study was conducted to provide longitudinal observational data for individual patients with persistent symptoms of schizophrenia. Pattern is an international, multicenter, non-interventional, prospective cohort study of schizophrenia outpatients who were not considered to be in recovery. In the longitudinal phase reported herein, patients were assessed over 1 year using different clinical rating scales. Patient management followed routine local clinical practice. Primary outcome was disease state, defined by the Positive and Negative Syndrome Scale (PANSS), Negative Symptom Factor Score (NSFS), Positive Symptom Factor Score (PSFS), and Personal and Social Performance (PSP) Scale. In total, 1344 protocol-compliant patients (70.9% male) were included. Patients showed a high stability in disease state between consecutive study visits. Persistent negative persistent symptoms and symptomatic remission were the most prevalent and stable disease states. Patients in relapse generally transitioned to negative persistent symptoms or to symptomatic remission. PANSS, PSP, and quality of life ratings remained relatively stable. Relapses occurred in 10% of patients; probability of relapse was associated with younger age, extra-pyramidal symptoms, and more antipsychotic medications. Despite treatment, schizophrenia symptoms tend to remain stable over time, without overall improvement. One of the greatest challenges in schizophrenia is attainment of full symptom remission.